Acceptance Behavior of Electronic Prescription System - Sidiq, Rapitos (KEMAS: Jurnal Kesehatan Masyarakat, 2017)
Electronic prescription is one of information systems to support medical services based on computer technology to support clinical decision (Clinical Decision Support, CDS). Studies proved that the use of this system can decrease medication error. One of the hospitals that have applied this system is Meuraxa Hospital. This study aimed to determine the acceptance behavior of electronic prescription information systems. The respondents of this study were 30 doctors at specialist clinic. Data was collected by distributing questionnaires on August 1st-23rd, 2016. Data was processed using SmartPLS 3.0. Results showed that there was a positive effect of effort expectancy factor on behavioral intention and facilitating factors on the use behavior towards receipt of electronic prescription. It is expected that the management of Meuraxa hospital develop an existing electronic prescription system by accommodating the needs of the system users.